Etomidate versus ketamine for procedural sedation in paediatric Patients in the emergency department - Fatan, Ahmad Abdulbasitz Ahmad (2012)
Etomidate versus ketamine for procedural sedation in paediatric patients in the Emergency Department. The objectives of the study was to compare the sedation time (Ti) between Etomidate versus Ketamine and the safety of both drugs in the procedural sedation and analgesia among paediatric patients in Emergency department. A single blinded, randomized control study was conducted in Emergency Department Hospital Universiti Sains Malaysia, Kubang Kerian Kelantan, from 1s’ Jun 2010 untill 31st May 2011. 29 paediatric patients aged from 2 years old until 12 years old were recruited with the permission of their parents. They were randomized to two group, Etomidate group which received IV Fentanyl 1pg/kg plus IV Etomidate 0.2mg/kg and Ketamine group which received IV ketamine 1.5mg/kg. 13 patients randomized to Etomidate group and 16 patients to Ketamine group. Sedation time (Tj) was measured from the start of administrating the sedation drug until patients achieved adequate sedation which is characterized by Ramsay sedation score of 4. Vital sign was monitored and any adverse events documented until patients safely discharged/ admitted. From 29 subjects, only 23 subjects able to achieved adequate sedation level with the study drugs. All subjects who did not achieved adequate sedation level were from Etomidate group. From those 23 subjects, median Ti for Etomidate group was 5.0 minutes (IqR 9.0). In the Ketamine group, the median Ti was 1.5 minutes (IqR 4.0). There was no statistical difference in the Ti between the Etomidate group and Ketamine group (P value = 0.17). In this study, the adverse event that has been documented was retching and vomiting and the incidence between the two groups of study drug was similar and no significant difference. (P value = 0.53). There was no serious adverse effect documented during this study. This study proved that sedation time between Etomidate and Ketamine for the PSA were not significantly differ and Etomidate was less effective for PSA compared to the Ketamine in the paediatric age group. Nevertheless, both groups of sedative agents were relatively safe to be used without any serious adverse effect in the paediatric population in Malaysia.